The international jurisdiction rule contained in article 10 of the Council Regulation (EC) 2201/2003: Scope and conditions of its application - Herranz Ballesteros, Mónica (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The interpretation of article 10 of the Brussels II bis Regulation is the purpose of this paper. Article 10 allows, on the one hand, to maintain the jurisdiction of the authorities of the habitual residence before the wrongful removal or retention of the child and, on the other hand, permits to transfer the jurisdiction to the authorities of the State where the child has been removed when its conditions have been satisfied. The interpretation of article 10 is controversial. This paper deals with its territorial scope, the requirements and conditions for its application through the interpretation of the European Court of Justice case law.
Keywords: Brussels II bis Regulation; international jurisdiction in international abduction cases; territorial scope; requirements for the application of article 10